Waiting time for specialized outpatient access in high-risk prenatal care: a mixed-method study (Research, Society and Development, 2022)
Objective: to analyze the waiting time for specialized outpatient access for high-risk prenatal care. Methodology: mixed method study with sequential explanatory design. In the quantitative stage, an analytical cross-sectional study was carried out with 319 postpartum women during their hospital stay, using a semi-structured instrument and interview, followed by descriptive and analytical analysis using the Chi-square test (p≤0,05). In the qualitative phase, the study was guided by Social Phenomenology with 13 managers of indirect assistance in high-risk prenatal care, through an audio-recorded face-to-face interview and analyzed in the light of Social Phenomenology. Results: the waiting period for accessing the specialized service was 15 days (32,3%), 16 to 30 days (27,9%), over 90 days (9,4%) and (19,1%) not had access to the outpatient service. The results showed as factors that influence the waiting time: insufficient vacancies, incomplete or non-monitoring of information and non-compliance with the referral criteria. The managers pointed out that the health team needs to have enough knowledge to develop their actions with reciprocal intentions in the care and care process. Conclusion: the first consultation in a specialized service takes place over a long period of time and some women cannot even access the service, resulting in exclusive care in primary care, which is not organized to assume exclusive care for high-risk pregnant women.